KONSEP PENDIDIKAN ETIKA DALAM BERIBADAH (KAJIAN Q.S AL-ISRA AYAT 110) - Deka Igus Saputri; Maryono Maryono; Akhmad Khoiri (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The purpose of this study is to: 1. (Al Isro:110. 2. Determine the relevance of ethics education in worship. 3. To clarify the background of the concept of ethics education in contemporary worship."This study is a descriptive study, which means that questionnaires or literature searches were used to collect data. both primary and secondary data were used to gather study material. The Qur'an Karim and some of our commentary serve as the primary sources of knowledge. Books, newspapers, journals, internet media, and other materials that are relevant to the thesis subject serve as secondary data sources. The Al-Quran, the Tafsir, and other significant texts are employed as documents as part of the documentation data collecting approach. Textual information is analyzed using both content analysis and discourse analysis. The goal of content analysis is to make the book's contents clear. Discourse analysis, a different approach owing to the constraints of content analysis, studies the meaning of communications with an emphasis on covert (latent) meanings.The following conclusions may be drawn from the author's research findings: (1) Moral instruction in worship is regarded as one of the most crucial aspects of human existence, according to the interpretation of QS. Al-Isra verse 110.(2) The idea of character education in worship refers to human customs or conduct based on the course of action or rules established by Allah SWT.(3) Setting the idea of education at the forefront of growth or the contemporary morals or ethics of the millennial generation,